Unlocking idle waqf assets through institutionalized pentahelix collaboration: Evidence from North Sumatra, Indonesia - Lubis, Irma Suryani; Marliyah, Marliyah; Ramadhan, Muhammad (Universitas Islam Indonesia, 2025)
IntroductionWaqf, an Islamic endowment intended for perpetual public benefit, remains one of the least-leveraged instruments of regional development in Indonesia. In North Sumatra a large share of endowed land is legally uncertified and economically idle, reflecting weak managerial capacity and fragmented multi-stakeholder coordination.ObjectivesThis study investigates whether an institutionalized Pentahelix governance framework, uniting academia, business, community, government, and media, can transform dormant waqf assets into productive ventures that advance sustainable socio-economic goals.MethodA sequential-exploratory case-study design combined forty semi-structured interviews, extended participatory observation in five waqf institutions, and systematic document analysis of legal records, financial reports, and policy papers. Data were coded thematically using Miles and Huberman’s interactive model, displayed in cross-stakeholder matrices, and triangulated to strengthen analytic credibility.ResultsFive mutually reinforcing bottlenecks emerged: limited public literacy, low professional competence among nazhir (waqf managers), protracted land-title certification, the absence of an integrated digital registry, and ad-hoc stakeholder collaboration. Universities and government agencies show relative engagement, whereas businesses and media remain peripheral, leaving community actors to operate in isolation. A five-lever blueprint, regional synergy forum, professional certification pathways, province-wide digital ledger, targeted fiscal incentives for corporate waqf, and sustained media literacy campaigns, offers an actionable route to align legal certainty, data transparency, and participatory governance.ImplicationsImplementing the proposed blueprint would unlock latent economic value, strengthen public trust, and align North Sumatra’s waqf sector with national Islamic-finance reforms and the United Nations Sustainable Development Goals. The model balances religious legitimacy with market discipline, demonstrating how social-justice mandates can coexist with competitive financial performance.Originality/NoveltyBy integrating “hard” infrastructural prerequisites, secure certification and digital systems, with “soft” relational capital generated through Pentahelix collaboration, the research extends existing theory and supplies a replicable governance template for Islamic social finance.